Is The Human Development Index Effects The Poverty Rate in Indonesia 2020? - Agus Riyanto (Khazanah: Jurnal Mahasiswa, 2022)
Poverty is a serious problem faced by the Indonesian people from ancient times to the present. One that affects the level of poverty in Indonesia is the Human Development Index (IPM). Therefore, it is necessary to research the influence of HDI on the poverty level of each province in Indonesia. The purpose of this study is to analyze the effect of the Human Development Index on poverty levels in Indonesia. This study uses a quantitative approach with a descriptive analysis method. In addition to descriptive analysis, this study uses a simple linear regression analysis method to determine the effect of the human development index on the poverty rate in Indonesia. The preliminary findings of this study conclude that the human development index affects the poverty level of - 0.899. This means that the higher the Human Development Index, the lower the poverty level. From R square shows that 42.8 percent of the Human Development Index variable explains the poverty variable, while the rest can be explained by other factors. This finding is expected to provide recommendations to the government regarding human development. Keywords: Human development index, poverty rate, regression